STUDY OF ACID-BASE PROPERTIES OF PHOSPHORUS-CONTAINING TUNGSTEN MELTS UNDER EQUILIBRIUM CONDITIONS - Malyshev, Viktor; Shakhnin, Dmytro; Gab, Angelina (Scientific Journal "Metallurgy", 2024)
The ionic composition of tungstate melts determines both the nature of electrode processes and equilibria, as well as the composition of cathode products. The activity of oxygen ions in the tungstate melt was studied by measuring the EMF of electrochemical cells with oxygen electrodes. A diaphragm-type platinum-oxygen electrode was used as a reference electrode. The indicator platinum electrode was immersed in the investigated melt. Potentiometric studies proved that P2O5, NaPO3, Na4P2O7 compounds are acceptors of oxygen ions, and Na3PO4 is a donor. The character of experimental dependences of the platinum-oxygen electrode on the concentration of oxygen-containing phosphorus compounds can be justified using the theory of conjugated acids-bases. Studies have shown that, when P2O5, NaPO3, Na4P2O7 are added to the tungstate melt, W2O7 2- anions are formed which is confirmed by structural methods of study of frozen melts. The agreement of the experimental and calculated dependences confirms the correctness of the proposed models of the ionic composition of melts. The possibility to control the acid-base properties of these melts is important from the point of view of tungsten electrodeposition and high-temperature electrochemical synthesis of tungsten carbides, borides, and silicides. Information on the structure of tungstate melts with oxygen-containing compounds of phosphorus makes it possible, depending on the conditions of electrolysis, to obtain purposefully tungsten deposits in the form of powders or coatings.